The effect of prolonged etiolation inside the cabbage (Brassica oleracea L. cv. capitata) head and the greening of the different leaf layers - Solymosi, Katalin (Acta Biologica Szegediensis, 2005)
The outer leaves of white cabbage act as optical filters and decrease the light intensity considerably inside the cabbage head. As a consequence, the inner leaf primordia develop under prolonged etiolation conditions. The detailed analysis of plastid ultrastructure and chlorophyll biosynthesis of the different leaf layers of cabbage head was done in Solymosi et al. (2004). The innermost leaves contained multifunctional proplastids with starch grains, phytoferritin and poorly developed, concentrically arranged perforated membranes. Rarely, also prolamellar body was observed in the leaves. Photoactive and non-photoactive protochlorophyllide forms were present in the innermost primordia, their fluorescence emission spectra were similar to those of very young leaves or to slowly greening, non-leaf organs. The leaves in the 4th leaf layer contained chloroplasts with poorly differentiated grana. Their spectra indicated the presence of chlorophyll-protein complexes of both PSI and PSII. In the leaves of the 10th leaf layer proplastids were present and the leaves contained chlorophyll and protochlorophyllide, too. These leaves were illuminated during their earlier developmental stage and became etiolated only later. The greening of these three different leaf layers was compared in order to study, how plastid differentiation occurs in the differently developed leaves. The greening process of young and old (three, four month old - stored) cabbage heads was analyzed.